PENGELOLAAN ALOKASI DANA DESA DALAM MEWUJUDKAN GOOD GOVERNANCE - Ade Setiawan (Among Makarti, 2019)
AbstractThis study aims to know the management of the Village Fund Allocation (ADD) in achieving good governance (accountability, transparency and participation) ranging from planning, implementation and accountability. This study uses qualitative descriptive method with case studies, which describe the management of the Village Fund Allocation (ADD) in rural Ngombakan then compared with the applicable regulations (Permendagri No. 113/2014), and crosscheck with real phenomenon that occurs in the management of the Village Fund Allocation (ADD) in rural Ngombakan realize good governance, so that it can be withdrawn conclusion. The results of this study indicate that the management of ADD in the Ngombakan village outline has been accountable, transparent, and participatory. However, technically there are still obstacles. These constraints are an obstacle from districts that are late in making the Bupati Regulation regarding the regulations on ADD and its management. This has an impact on the delay in reporting related to ADD management in Ngombakan Village. Keywords : Dana desa, Good Governance